Current and voltage transfer function filters using a single active device - Sagbas, M.; Ayten, U. E.; Sedef, H. (INST ENGINEERING TECHNOLOGY-IET, 2010)
In this study, current and voltage transfer function filters using single active component, namely, current backward transconductance amplifier (CBTA) are presented. The proposed structures are a single-input three outputs (SITO) current-transfer function filter, a single-input four-output (SIFO) voltage transfer function filter and three-input single-output (TISO) voltage transfer function filter. The proposed filters have low active and passive sensitivities and use canonical number of electronics components. The validity of the proposed circuits is demonstrated by PSPICE simulations and experimental results. Operation range of the CBTA and its parasitic effects are also discussed.
Keywords: UNIVERSAL-BIQUADRATIC-FILTERS; HIGH INPUT IMPEDANCE; CURRENT-MODE; MINIMUM NUMBER; REALIZATION; Engineering